Development of Agarwood Oil Research and Benefit: Bibliometric Analysis - Saputra, Hendra; Satria, Benni; Nazir, Novizar; Anggraini, Tuty (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Agarwood oil, derived from the fragrant resinous wood of the Aquilaria and Gyrinops trees, has attracted great attention due to its diverse pharmacological properties and commercial value. The complex chemical composition of agarwood oil, consisting of more than 150 chemical compounds, has been linked to its therapeutic potential in treating chronic inflammatory diseases, anxiety, depression, and insomnia. This research uses exploratory, descriptive research. The research used in this research is the literature study method regarding the development of agarwood oil research and its benefits. Documents from the Scopus website are saved in the following form: RIS-type files. Analysis was conducted using VOSviewer 1.6.18 for Windows software. The research results show that there has been a decline in the trend of research on agarwood oil over the last 10 years; most research on agarwood oil has been carried out by Malaysia and China and followed by Japan. Research has revealed numerous benefits of agarwood oil, indicating its potential for development into derivative goods, particularly in the health and fragrance industries.